PROVOCĂRILE ACCESULUI DESCHIS ȘI VIZIBILITATEA PRODUCŢIEI ȘTIINŢIFICE A REPUBLICII MOLDOVA - ŢURCAN, Conf. univ. dr., Universitatea de Stat din Moldova, Nelly (BIBLIOPOLIS, 2020)
Based on indicators of scientifi c productivity calculated by Journal SCImago & Country Rank and Thomson ISI this article evaluates Moldovan’s position regarding the number of scientifi c papers. Also article presents the data regarding the Moldovan scholars’ collaboration in scientifi c publishing. The article features the Open Access initiative and presents opportunities for extension of scientifi c visibility by applying open access strategies.